Code-Mixing As a Communicative Strategy Among International Passengers and Employees in Hasanuddin International Airport Makassar - Andi Kurniadi Baskal; Sujarwo; Muhammad Yahrif (CV. Eureka Murakabi Abadi, 2024)
The use of English in service operations is very necessary in communicating with service users who not only come from Indonesia but also from abroad. Therefore, the use of English is very important in-service operations at the airport. This research aims to analyze code mixing as a communication strategy among passengers and employees at Hasanuddin International Airport. The design of this research was qualitative research. It is called collaborative qualitative because the research directly involves employees and international passengers as respondents. The research results show that there are three types of code mixing, namely alternation, congruence, and lexicalization. Respondents participated in interviews, which yielded information about the variables that influence the use of code mixing in textual communication regarding code mixing as a communication strategy between employees and international passengers. There are seven factors that cause code mixing, namely (1) lack of mastery, especially mastery of English, (2) intention to increase prestige, (3) wanting to show off one's skills, (4) searching for identity, (5) habits, (6) want to joke (make jokes) and (7) relaxed conversation situation (formality). It can be concluded that this research identifies three forms of code mixing, namely substitution, congruence and lexicalization and this is influenced by several factors in the occurrence of code mixing among employees and international passengers